Analysis of Sales Growth and ROA in Tax Avoidance: Corporate Governance Perspective - Roy Frananda Saragih; Suyanto Suyanto; Yhoga Heru Pratama (Equity: Jurnal Ekonomi, 2025)
A recent comprehensive study reveals the complex dynamics of tax avoidance among manufacturing companies in the ASEAN region. The study, which covers 791 companies with a total of 4,746 research data over the period 2018-2023, provides a comprehensive overview of the parameters that determine tax avoidance. The authors discovered a favorable link between tax evasion behavior and sales growth using E-views 12 moderate regression analysis (MRA) statistical study. Conversely, there is a negative correlation between the practice and Return on Assets (ROA). The little influence of company governance in mitigating the association between sales growth and ROA on tax evasion is one intriguing discovery. This subject demonstrates the intricacy of the tax evasion process, which the corporate governance mechanism is unable to adequately explain. The results of this study make an important contribution to the academic and practical understanding of tax strategies in the ASEAN manufacturing business environment.